Gas flooding adaptability of deep low permeability condensate gas reservoir - LI Zhongchao, QI Guixue, LUO Bobo, XU Xun, CHEN Hua (Youqicang pingjia yu kaifa)
The transition from depletion mining to gas flooding in deep low permeability condensate gas reservoirs poses significant adaptability challenges. To address these, a series of evaluation studies were conducted using the Pressure-Volume-Temperature（PVT）analyzer, long core displacement physical simulation technology, and numerical simulation calculations. This research specifically examines the impacts of CO2 injection, natural gas（associated gas or pure CH4）, and nitrogen（N2）on the high-pressure physical properties of condensate gas systems and their potential to improve condensate oil recovery. Comparative analyses reveal that CO2, due to its high solubility and favorable gas-oil dissolution ratio in condensate oil, significantly reduces the saturation pressure and dew-point pressure of condensate gas reservoirs, thereby offering the most substantial improvement in oil recovery rates. Further optimization studies using long core physical simulation technology focused on injection timing, modes, and rates for CO2 flooding. It was determined that pulsed gas injection strategies are particularly effective when implemented above the dew-point pressure. These findings provide essential data to support the formulation of technical policies and field plans for gas injection development in such challenging reservoir conditions.